The Cold War : Historiography, Memory, Representation - Etges, Andreas (2017)
The traces of the Cold War are still visible in many places all around the world. It is the topic of exhibits and new museums, of memorial days and historic sites, of documentaries and movies, of arts and culture. There are historical and political controversies, both nationally and internationally, about how the history of the Cold War should be told and taught, how it should be represented and remembered. While much has been written about the political history of the Cold War, the analysis of its memory and representation is just beginning. Bringing together a wide range of scholars, this volume describes and analyzes the cultural history and representation of the Cold War from an international perspective. That innovative approach focuses on master narratives of the Cold War, places of memory, public and private memorialization, popular culture, and schoolbooks. Due to its unique status as a center of Cold War confrontation and competition, Cold War memory in Berlin receives a special emphasis.